AlSi powder material and preparation method and application thereof
By using Er and Zr to replace Sc in Al-Si alloy, combined with inert gas atomization method and laser selected melt additive manufacturing technology, the problems of material strength and cost of Al-Si alloy are solved, and efficient and economical preparation results are achieved.
Patent Information
- Application Number
- CN202411681226.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The tensile strength and yield strength of the existing Al-Si alloy materials are insufficient, the elongation is low, and the preparation cost is increased due to the addition of Sc metal.
By adding metal Er and metal Zr to the Al-Si alloy system to partially or completely replace Sc, the content of each metal component is strictly controlled, AlSi powder material is prepared by inert gas atomization method, and the preparation is prepared by laser selection melt additive manufacturing technology.
The mechanical strength and elongation of the Al-Si alloy system are improved, the preparation cost is reduced, and the application needs of the medium-strength aluminum alloy market is met.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an AlSi powder material and a preparation method and application thereof. Background Art
[0002] Metal additive manufacturing technology, also often referred to as metal 3D printing technology, has played an increasingly important role in the development of modern industry in recent years. Compared with traditional processing technologies such as casting, forging, extrusion, welding, and machining, metal additive manufacturing technology, which has the characteristics of direct manufacturing of complex structures and integrated forming of high-performance material preparation, is subverting the traditional design and manufacturing methods of high-end equipment to form unprecedented innovative solutions.
[0003] In the metal additive manufacturing industry chain, the material side has received more and more attention, because the application side drives the material side to upgrade, and the material side enables the development potential of metal additive manufacturing. With the continuous improvement of ultra-light design standards in strategic emerging industries such as aerospace, military industry, new energy vehicles, and electronic information, high-strength aluminum alloy powder for metal additive manufacturing has become a mainstream material for metal additive manufacturing and occupies an important place in the field of industrial manufacturing.
[0004] Although the prospects for high-strength aluminum alloy powders for additive manufacturing are promising, the bottleneck problems are prominent. First, traditional high-performance deformed aluminum alloys cannot be directly used in laser additive manufacturing technology: the laser additive manufacturing process involves the coupling of multiple physical fields such as temperature field and stress field. It is essentially a comprehensive process of rapid solidification and reciprocating thermal cycles, with high molten pool temperature, uneven temperature distribution in the molten pool, remelting and high cooling rate. The above characteristics make traditional aluminum alloys prone to forming coarse, textured columnar grains during rapid non-equilibrium solidification, leading to thermal cracks, anisotropy of performance and other problems; second, the existing mainstream high-performance aluminum alloy powders for additive manufacturing are far from meeting the needs of high-service application scenarios, but cannot meet specific needs. At the same time, the manufacturing parameters in the printing process will also introduce defects related to geometry, surface integrity and microstructure, which will further reduce the mechanical properties of the formed material such as strength and ductility.
[0005] In the field of aluminum alloy powder materials, the application fields can be different according to the different mechanical properties of aluminum alloys. For example, medium-strength aluminum alloys (200~400MPa) are widely used in the automotive and civil industrial fields, and are widely used in the preparation of shoe molds, car bodies, wheels, suspension systems, etc. High-strength aluminum alloys (≥480 MPa) occupy a very important position in the aviation industry and are one of the main structural materials in the aviation industry. Ultra-high-strength aluminum alloys (500~900MPa) are widely used in aviation, aerospace, automobiles, ships and other fields due to their high strength and good corrosion resistance. Aluminum alloys with different properties can be obtained according to the application in different fields.
[0006] The classification system of aluminum alloys in the United States is based on the main added elements in the alloys, and aluminum alloys are divided into different systems, including: pure aluminum, Al-Cu alloys, Al-Mn alloys, Al-Si alloys, Al-Mg alloys, Al-Mg-Si alloys, Al-Zn-Mg alloys and other alloys. The categories of high-strength aluminum alloy powders for laser additive manufacturing are mainly concentrated in the Al-Si alloy system and the Al-Mg alloy system. Among them, the Al-Si alloy system has the characteristics of low melting point and narrow solidification temperature range. It is currently the most suitable aluminum alloy for laser additive manufacturing. At present, it is mainly represented by near-eutectic alloys represented by A1Si10Mg, AlSi7Mg and AlSi12. However, the tensile strength of the system material is only 300 MPa, and the yield strength is only 200 MPa. The strength is relatively low, especially for the application of structural components with high load-bearing stress, it cannot meet the application requirements.
[0007] CN107695338A discloses an AlSi7Mg powder material, a preparation method thereof and an application thereof. The invention mainly relates to an AlSi7Mg powder material for 3D printing and a preparation method thereof, wherein the mass fraction of the main alloying elements in the powder material is: Si, 4.5-9.5%, Mg, 0.25-0.95%, Ti, 0.01-0.45%, and the balance is aluminum. The powder material is prepared by an inert gas atomization method, and the tensile strength of the printed part is about 300MPa, the yield strength is about 200MPa, and the elongation is about 9.0%. This technical solution has improved the performance of the material to a certain extent, but its strength is still insufficient. CN112048647A discloses an Al-Si-Mg-Sc-Zr aluminum alloy powder for laser additive manufacturing, which discloses an Al-Si-Mg-Sc-Zr aluminum alloy powder for laser additive manufacturing and its application. The aluminum alloy powder for laser additive manufacturing has the following components by mass fraction: Si: 6.0~8.0%, Mg: 0.60~0.80%, Ti: 0.10~0.20%, Sc: 0.1~0.6%, Zr: 0.1~0.4%, and the remainder is Al and inevitable impurities. In this scheme, the density of the sample formed by SLM of the Al-Si-Mg-Sc-Zr aluminum alloy powder can reach more than 99.9%, the tensile strength of the deposited sample exceeds 440MPa, the elongation after fracture of the sample after heat treatment exceeds 10%, and there is no obvious anisotropy, which can meet the needs of application in related fields. However, the Sc used therein is expensive and has a small precipitation driving force, so it cannot be widely promoted and applied.
[0008] The mechanical properties of Al-Si alloy systems are usually regulated by composition modification based on stoichiometric changes, addition of strengthening particles or microalloying. Although the refinement of the eutectic network structure, the narrowing of the temperature range of alloy solidification and the use of solid solution strengthening to enhance the mechanical properties can be induced by changing the Si and Mg contents, the content regulation is limited, otherwise a high crack density will be generated. The high-strength Al-Si alloys currently introduced for additive manufacturing mainly improve their mechanical properties by in-situ regeneration or Sc microalloying. By adding strengthening particles such as ceramics and carbon-based materials, in-situ generation of heterogeneous nucleation particles is used to increase the nucleation rate and pin the grain boundaries to limit the growth of α-Al, and the transformation of columnar crystals to equiaxed crystals is promoted to reduce the tendency of hot cracking. Although the tensile strength is enhanced, the introduction of strengthening particles by mixing powders may cause uneven particle distribution and destruction of powder morphology, and composition segregation is difficult to avoid, resulting in defects and anisotropy of properties. In addition, the density difference between the strengthening particles and the aluminum matrix, the wettability matching problem and the reactivity will lead to the obstruction of the atomization process, the formation of defects and the loss of strengthening particles. Microalloying based on the rare earth element Sc can avoid the above problems. The modification and refinement of Sc on α-Al crystals and eutectic Si structures and the second phase strengthening effect of the nano-precipitated phase during heat treatment can promote the nucleation of equiaxed crystals during alloy solidification, thereby obtaining an ultrafine eutectic structure and significantly improving the mechanical properties. However, the expensive price and small reserves of Sc increase the preparation cost and limit its large-scale industrial application. In addition, the maximum solid solubility of Sc in the equilibrium state is 0.35%, which limits its maximum precipitation strengthening effect.
[0009] In summary, developing new 400 MPa grade Al-Si alloy materials and reducing their production costs have far-reaching significance and urgent market demand for broadening the types of Al-Si alloy powders and the application of additive manufacturing technology in the medium-strength aluminum alloy market. This can not only meet the requirements of high-performance materials for high-end industrial applications, but also promote the further popularization and application of additive manufacturing technology. Summary of the invention
[0010] The main purpose of the present invention is to provide an AlSi powder material and a preparation method and application thereof, so as to solve the problems of insufficient tensile strength, yield strength and low elongation of Al-Si alloy materials in the prior art, as well as increased preparation cost of AlSi powder materials due to the addition of more Sc metal, aiming to develop a new 400 MPa grade Al-Si alloy material and reduce its production cost to meet its application in the medium-strength aluminum alloy market.
[0011] In order to solve the above problems, the present invention provides an AlSi powder material, which includes the following components in weight percentage: Si: 6.5%~7.5%, Mg: 0.5%~0.7%, Zr: 0.7%~1.1%, Sc: 0.0%~0.5%, Mn: 0.0%~1.6%, Er and the balance Al; and when the content of Sc is 0.0%, the content of Er is 0.9%~1.4%; when the content of Sc is not 0.0%, the content of Er is 0.0%~0.5%.
[0012] Furthermore, the AlSi powder material includes the following components by weight percentage: Si: 6.5%~7.5%, Mg: 0.5%~0.7%, Er: 1.0%~1.4%, Zr: 0.9%~1.1%, Mn: 1.2%~1.6%, and the balance is Al.
[0013] Furthermore, when the Sc content in the AlSi powder material is 0.0%, the content ratio of Er to Zr is 1.1-1.8; preferably, when the Sc content in the AlSi powder material is 0.0%, the content ratio of Er to Zr in the AlSi powder material is 1.2-1.5.
[0014] Furthermore, when the Sc content in the AlSi powder material is not 0.0%, the sum of the Sc and Er contents is 0.8-1.0%.
[0015] According to another aspect of the present invention, a method for preparing an AlSi powder material is also provided, and the preparation method comprises the following steps: weighing the required alloy raw materials according to the component content of the material to be prepared, placing them in a smelting device, and making the vacuum degree of the smelting device ≤50Pa; after replacing the gas in the smelting device with an inert gas, smelting and refining the alloy raw material mixture to obtain an aluminum alloy melt; atomizing the aluminum alloy melt to make powder and screen the particle size to obtain an AlSi powder material.
[0016] Furthermore, when the AlSi powder material contains metal Sc, the melting temperature is 850~950℃, and the melting time is 15~30min; the refining temperature is 850~950℃, and the refining time is 10~15min; preferably, when the AlSi powder material does not contain metal Sc, the melting temperature is 900~950℃, and the melting time is 15~30min; the refining temperature is 900~950℃, and the refining time is 10~15min; preferably, the raw materials in the smelting device are placed from bottom to top with gradually decreasing density; preferably, the alloy raw materials include aluminum silicon alloy, aluminum erbium alloy, aluminum zirconium alloy, aluminum manganese alloy, metal aluminum, metal magnesium and optional aluminum scandium alloy; preferably, the inert gas is argon, and its purity is greater than or equal to 99.99%.
[0017] Furthermore, during the atomization powder making process, the atomization pressure is 2.5-3.2 MPa, the atomization temperature is 850-900° C., and the atomization gas is argon.
[0018] Furthermore, the volume fraction of the AlSi powder material having a particle size range of ≤75 μm is ≥97%.
[0019] According to a third aspect of the present invention, there is also provided an Al-Si alloy part, which is prepared from the above-mentioned AlSi powder material.
[0020] According to a fourth aspect of the present invention, a method for preparing an alloy part is also provided, the preparation method comprising: using laser selective melting additive manufacturing technology to print a part and perform heat preservation treatment to obtain an Al-Si alloy part; preferably, the part printing process parameter range is: the oxygen content of the printing chamber is 0.08~0.1%, the pressure of the printing chamber is 23~27mbar, the fan flow rate is 2.3m / s~2.7m / s, the substrate preheating temperature is 80~120°C, the thickness between printing layers is 30~50μm, the scanning spacing is 100~120μm, and the interlayer rotation angle is 67°; preferably, the temperature of the heat preservation treatment process is 165~200°C, and the time is 6~8h; preferably, the scanning power during the part printing process is 260~320W; preferably, the scanning speed during the part printing process is 1400~1800 mm / s.
[0021] The present invention provides an AlSi powder material, which includes the following components: Si: 6.5% to 7.5%, Mg: 0.5% to 0.7%, Zr: 0.7% to 1.1%, Sc: 0.0% to 0.5%, Mn: 0.0% to 1.6%, Er and the balance Al; and when the content of Sc is 0.0%, the content of Er is 0.9% to 1.4%; when the content of Sc is not 0.0%, the content of Er is 0.0% to 0.5%. The present invention adds metal Er and metal Zr to the Al-Si alloy system to partially or completely replace the metal Sc therein, and strictly controls the content of each metal component within the above range, so as to give full play to the synergistic effect between the various metal components, thereby achieving the purpose of improving the mechanical strength of the Al-Si alloy system and improving its elongation. In addition to the synergistic effect between the above-mentioned metal components, the addition of rare earth metals Er and Zr plays an important role in improving the mechanical properties and elongation of AlSi powder materials. First, the rare earth metal Er has a low solid solubility in the Al matrix. This feature makes it easy to be repelled to the front of the solid-liquid interface during the crystallization process, resulting in enrichment. The enrichment of rare earth metal Er at the solid-liquid interface can reduce the probability of metal Si and metal Mg entering the solid solution, effectively inhibit the growth of unit cells, and can not only reduce the length and short axis of columnar crystals, but also promote the formation of equiaxed crystals, which can effectively improve the mechanical properties of the material. Second, the smaller solid solubility of metal Er in the Al matrix indicates that Al3Er has a stronger precipitation driving force and can precipitate a larger volume fraction. These phases have a high melting point and will not be completely melted during the remelting process at a relatively low temperature at the edge of the molten pool. They can be used as heterogeneous nucleation points to promote the formation of equiaxed crystals and refine the grains, thereby significantly improving the mechanical properties of the Al-Si alloy system. Third, metal Zr can form a kinetically stable L12Al3 (Er, Zr) phase with metal Er, which has a second phase strengthening effect and a recrystallization inhibition effect, which is beneficial to improving the mechanical properties of Al-Si alloys. In addition, adding abundant and inexpensive metal Er to replace metal Sc is of great significance for reducing the cost of AlSi powder materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0023] Figure 1 The SEM image of the AlSi powder material prepared according to Example 1 of the present invention is shown;
[0024] Figure 2 shows a particle size distribution diagram of the AlSi powder material prepared according to Example 1 of the present invention;
[0025] Figure 3 A hollow ratio diagram of the AlSi powder material prepared according to Example 1 of the present invention is shown;
[0026] Figure 4 The sphericity diagram of the AlSi powder material prepared according to Example 1 of the present invention is shown;
[0027] Figure 5 The SEM image of the AlSi powder material prepared according to Example 2 of the present invention is shown;
[0028] Figure 6 shows a particle size distribution diagram of the AlSi powder material prepared according to Example 2 of the present invention;
[0029] Figure 7 A hollow ratio diagram of the AlSi powder material prepared according to Example 2 of the present invention is shown;
[0030] Figure 8 The sphericity diagram of the AlSi powder material prepared according to Example 2 of the present invention is shown. DETAILED DESCRIPTION
[0031] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0032] As described in the background technology section, the Al-Si alloy system has the characteristics of low melting point and narrow solidification temperature range, and is currently the most suitable aluminum alloy for laser additive manufacturing. However, the tensile strength of the system material is only 300 MPa, and the yield strength is only 200 MPa. The strength is low and it is easy to break or deform. Especially for high-stress structural parts, it cannot meet the application requirements. Therefore, the development of new 400 MPa grade Al-Si alloy materials, while improving its tensile strength and yield strength, improving its elongation and reducing its production cost, has far-reaching significance and urgent market demand for broadening the types of Al-Si alloy powders and the application of additive manufacturing technology in the medium-strength aluminum alloy market.
[0033] In order to solve the above problems, the present invention provides an AlSi powder material, which includes the following components in weight percentage: Si: 6.5%~7.5%, Mg: 0.5%~0.7%, Zr: 0.7%~1.1%, Sc: 0.0%~0.5%, Mn: 0.0%~1.6%, Er and the balance Al; and when the content of Sc is 0.0%, the content of Er is 0.9%~1.4%; when the content of Sc is not 0.0%, the content of Er is 0.0%~0.5%.
[0034] In the above AlSi powder material, Al is used as the metal matrix and metal Si is the main added component. By strictly controlling the addition ratio of metal Mg, metal Mn, metal Zr, metal Er and metal Sc within the above range, the synergistic effect between the various components in the material can be effectively exerted, so that the obtained AlSi powder material has good mechanical properties and elongation. By adding metal Er to the Al-Si alloy system to partially or completely replace the metal Sc therein, not only the mechanical strength of the Al-Si alloy system is improved, and the properties of the Al-Si alloy are improved, but also the addition of metal Er, which is rich in content and low in price, effectively reduces the dependence of AlSi on metal Sc, thereby reducing the preparation cost, which is conducive to the industrial scale application of AlSi powder materials.
[0035] In particular, the AlSi powder material of the present invention has good mechanical properties and elongation, and the rare earth metals Er and Zr therein play an important role. First, the rare earth metal Er has a small solid solubility in the Al matrix, which makes it easy to be repelled to the front end of the solid-liquid interface during the crystallization process, resulting in enrichment, and the enrichment of the rare earth metal Er at the solid-liquid interface can reduce the probability of metal Si and metal Mg entering the solid solution, effectively inhibit the growth of the unit cell, not only can reduce the length and short axis size of the columnar crystal, but also can promote the formation of equiaxed crystals, and can effectively improve the mechanical properties of the material. Second, the smaller solid solubility of Er in the Al matrix indicates that Al3Er has a stronger precipitation driving force, and a larger volume fraction of Al3Er phase can be precipitated. The precipitated Al3Er phase has a high melting point characteristic, and the remelting process at a relatively low temperature at the molten pool boundary will not be completely melted, and can be used as a heterogeneous nucleation point to promote the formation of equiaxed crystals, refine the grains and effectively inhibit the growth of the unit cell, thereby significantly improving the mechanical properties of the Al-Si alloy system. In particular, compared with the solid solubility of Sc element of 0.35wt%, the solid solubility of Er element is only 0.045wt%. The above-mentioned difference in solid solubility can make Er element more easily repelled to the front end of the solid-liquid interface than Sc element during the crystallization process, resulting in enrichment, thereby having a stronger grain refinement effect and improving the overall mechanical properties of the material. Thirdly, metal Zr can form a kinetically stable L12Al3 (Er, Zr) phase with metal Er. This crystal phase has a second phase strengthening effect and a recrystallization inhibition effect, which can be beneficial to further improve the mechanical properties of Al-Si alloys.
[0036] In summary, the AlSi powder material proposed in the present invention has good mechanical properties and high elongation, and also has the advantage of low preparation cost, which has far-reaching significance for broadening the types of Al-Si alloy powder materials and the application of additive manufacturing technology in the medium-strength aluminum alloy market. In particular, replacing the metal Sc in the AlSi powder material partially or completely with the metal Er not only improves its mechanical properties, but also further reduces the preparation cost of the AlSi powder material.
[0037] In a preferred embodiment, the AlSi powder material includes the following components: Si: 6.5%~7.5%, Mg: 0.5%~0.7%, Er: 1.0%~1.4%, Zr: 0.9%~1.1%, Mn: 1.2%~1.6%, and the balance is Al. Rare earth metal Er is abundant and inexpensive, and has a similar structure and strengthening mechanism to metal Sc, and also has the characteristics of smaller equilibrium solid solubility. Completely replacing metal Sc with rare earth metal Er, and controlling each component in the AlSi powder material within the above range, can make the AlSi powder material form a denser microstructure, have better mechanical properties and elongation, and can further reduce the production and preparation cost of the AlSi powder material.
[0038] In a preferred embodiment, when the content of Sc in the AlSi powder material is 0.0%, the content ratio of Er to Zr in the AlSi powder material is 1.1 to 1.8; in the AlSi powder material, the metal Er and metal Zr therein can form a kinetically stable L12Al3 (Er, Zr) phase, which has a second phase strengthening effect and a recrystallization inhibition effect. Controlling the addition ratio of metal Er and metal Zr within the above range can further improve the above effects, thereby making the obtained AlSi powder material have better performance. Preferably, when the content of Sc in the AlSi powder material is 0.0%, the content ratio of Er to Zr in the AlSi powder material is 1.2 to 1.5. Controlling the addition ratio of metal Er and metal Zr within the above preferred range can make the above effects better.
[0039] In a preferred embodiment, when the content of Sc in the AlSi powder material is not 0.0%, the sum of the contents of Sc and Er is 0.8-1.0%. The AlSi powder material proposed by the present invention uses metal Er to partially or completely replace the expensive metal Sc, so as to save production costs and improve material performance. When the AlSi powder material contains metal Sc, the sum of the contents of metal Sc and metal Er is within the above range, so that the AlSi powder material has better mechanical properties. At the same time, using metal Er to partially replace the expensive metal Sc can also achieve the purpose of reducing costs.
[0040] According to another aspect of the present invention, a method for preparing the above-mentioned AlSi powder material is also provided, and the preparation method comprises the following steps: weighing the required alloy raw materials according to the component content of the material to be prepared, placing them in a smelting device, and making the vacuum degree of the smelting device ≤50Pa; after replacing the gas in the smelting device with an inert gas, smelting and refining the alloy raw material mixture to obtain an aluminum alloy melt; atomizing the aluminum alloy melt to make powder and screen the particle size to obtain AlSi powder material.
[0041] In the preparation method of the above-mentioned AlSi powder material, the required alloy raw materials are first placed in a smelting device, and the vacuum degree of the smelting device is ≤50Pa. Then, an inert gas is used to replace the gas in the smelting device so that the oxygen in the device can be fully replaced, thereby avoiding the defects in the material caused by oxidation. Then, the alloy raw material mixture is first smelted and then refined to obtain an aluminum alloy melt. Finally, the obtained aluminum alloy melt is subjected to gas atomization powder making and particle size screening to obtain an AlSi powder material. The above-mentioned method is simple to operate and has strong feasibility, and can further improve the overall performance of the AlSi powder material.
[0042] In addition to the above steps, the gas atomization powder making process also includes the cleaning process of the smelting device before the placement and preparation of the raw materials to avoid the introduction of impurity elements and reduce the influence of moisture in the smelting furnace on the smelting process. In addition, the detection of the sealing of the smelting device is also an indispensable step to further avoid the oxidation of aluminum alloys, ensure the low oxygen and nitrogen content of the final product, and improve the product quality. When the vacuum degree of the smelting device is ≤50Pa, the airtightness of the device can be considered to meet the standard.
[0043] In a preferred embodiment, when the AlSi powder material contains metal Sc, the melting temperature is 850-950°C, and the melting time is 15-30min; the refining temperature is 850-950°C, and the refining time is 10-15min; preferably, when the AlSi powder material does not contain metal Sc, the melting temperature is 900-950°C, and the melting time is 15-30min; the refining temperature is 900-950°C, and the refining time is 10-15min. The present invention has found in a large number of experiments that the melting and refining temperatures have a great influence on the content of each component in the prepared AlSi powder material. The present invention sets the above two different melting and refining temperature ranges according to the component differences of the two different types of AlSi powder materials proposed. Melting and refining under the above conditions can make the prepared AlSi powder material and the pre-prepared component content more compatible, and can make the uniformity and stability of each component in the obtained AlSi powder material better. In addition, impurities in the alloy can be effectively removed, the purity of the material can be improved, and it has better mechanical strength. Preferably, the raw materials in the smelting device are placed with a density that gradually decreases from bottom to top. During the smelting process of the raw materials, the raw materials are placed in the principle of "sparse on top and dense on bottom" so that the stacking density gradually decreases from bottom to top, which can prevent the bridging effect from affecting the uniformity of the final AlSi powder material, and is conducive to further improving the mechanical properties of the AlSi powder material. Preferably, the alloy raw materials include aluminum silicon alloy, aluminum erbium alloy, aluminum zirconium alloy, aluminum manganese alloy, metal aluminum, metal magnesium and optional aluminum scandium alloy; preferably, the inert gas is argon, and its purity is greater than or equal to 99.99%. It should be noted here that considering that the burning of metal magnesium will consume part of the metal magnesium, in the actual preparation process, it is necessary to compensate for its mass, that is, to add 5~7% of its mass according to the content of the component to be prepared. Preferably, the inert gas is argon, and its purity is greater than or equal to 99.99%. Selecting high-purity argon can make the oxygen and nitrogen content in the prepared AlSi powder material lower and the performance better.
[0044] In a preferred embodiment, during the aerosolization powder making process, the aerosolization pressure is 2.5~3.2MPa, the aerosolization temperature is 850~900℃, and the aerosolization gas is argon. Controlling the aerosolization pressure and temperature in the aerosolization powder making process within the above range can make the sphericity of the prepared AlSi powder material better, help improve the fluidity of the material in the subsequent use process, and then promote the close bonding between the particles of the AlSi powder material; at the same time, it can also effectively reduce the hollow powder rate, avoid the generation of pores in the subsequent use process, and make the prepared alloy parts have better compactness and uniformity. In the aerosolization process, the diameter of the nozzle used can be selected according to the actual situation, and the preferred nozzle diameter is 5~8mm more suitable. The aerosolization speed can also be adjusted according to the actual situation, and the preferred aerosolization speed is 8~12 Kg / min.
[0045] In a preferred embodiment, the volume fraction of the prepared AlSi powder material in the particle size range of ≤75μm is ≥97%. Controlling the particle size of the AlSi powder material within the above range can ensure uniform distribution of the powder, good fluidity and high bulk density during the additive manufacturing process, which is beneficial to reducing defects inside the product and improving the strength of the product during the subsequent printing process. In addition, the obtained AlSi powder material also has the advantages of low impurity content, low oxygen and nitrogen content, high sphericity and low hollow powder rate.
[0046] According to the third aspect of the present invention, there is also provided an Al-Si alloy product, which is prepared from the above AlSi powder material. The Al-Si alloy product prepared from the above AlSi powder material has better mechanical properties and density.
[0047] According to the fourth aspect of the present invention, a method for preparing the above-mentioned Al-Si alloy product is also provided, wherein the laser selective melting additive manufacturing technology is used to print the product and perform thermal insulation treatment to obtain the Al-Si alloy product; preferably, the product printing process parameter range is: the oxygen content of the printing chamber is 0.08-0.1%, the pressure of the printing chamber is 23-27 mbar, the fan flow rate is 2.3 m / s-2.7 m / s, the substrate preheating temperature is 80-120°C, the thickness between the printing layers is 30-50 μm, the scanning spacing is 100-120 μm, and the interlayer rotation angle is 67°. AlSi powder materials will undergo a series of complex non-equilibrium physical state change processes such as melting, solidification, vaporization, and solid phase change during the laser additive manufacturing process, and high temperature gradients, high cooling rates, and reciprocating thermal cycles can easily lead to large residual stresses, cracks, holes, and other defects inside the structure, thereby limiting its serviceability. By using laser selective melting additive manufacturing technology, using the AlSi powder material proposed in the present invention, and combining with the above-mentioned preparation parameters, the Al-Si alloy parts prepared not only have good density, no crack defects in the organization, but also have suitable tensile strength and yield strength and good elongation. Preferably, the temperature of the heat insulation treatment process is 165~200℃, and the time is 6~8h. The heat insulation of the printed Al-Si alloy parts is conducive to eliminating the internal stress generated by factors such as uneven material shrinkage and temperature changes during the printing process, thereby reducing or eliminating deformation and cracking. Preferably, the scanning power during the printing process of the parts is 260~320W; preferably, the scanning speed during the printing process of the parts is 1400~1800 mm / s. Controlling the scanning power and scanning speed during the printing process of the parts within the above range can ensure that the parts form a dense microstructure during the printing process, reduce internal defects, and improve the mechanical properties and density of the parts.
[0048] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0049] The raw materials used in the embodiments and comparative examples need to be further described here. The purity of aluminum metal is ≥99.99%; the purity of magnesium metal is ≥99.99%; the purity of Al-20Si alloy is ≥99%, and the mass percentage of Si is 20%; the purity of Al-5Er alloy is ≥99%, and the mass percentage of Er is 5%; the purity of Al-10Zr alloy is ≥99%, and the mass percentage of Zr is 10%; the purity of Al-10Mn alloy is ≥99%, and the mass percentage of Mn is 10%; the purity of Al-5Sc alloy is ≥99%, and the mass percentage of Sc is 5%. Considering the burning loss of magnesium metal during the smelting process, it is necessary to compensate for its mass in the actual preparation process of AlSi powder material. The embodiments and comparative examples of the present invention all add 5% more mass of magnesium metal according to the content of the component to be prepared.
[0050] Example 1
[0051] (1) Prepare AlSi powder material, the composition and mass percentage of which are: Al-7Si-0.6Mg-1.2Er-0.8Zr.
[0052] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is smelted at 920℃ for 20min, and then refined at 920℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 900℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, wait for the powder to cool down to room temperature 25°C, and then place the obtained powder on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm is ≥98.04%, and D10 is 22.1μm, D50 is 37.2μm, and D90 is 60.8μm, with a powder yield of 25%.
[0053] The AlSi powder material prepared in Example 1 was tested, and its SEM image is as follows: Figure 1 The particle size distribution diagram is shown in Figure 2 As shown, Figure 3 The hollow ratio diagram of AlSi powder material is shown. Figure 4The sphericity diagram of AlSi powder material is shown. Figure 1 From the SEM image, it can be seen that the AlSi powder material prepared in the embodiment has a good spherical morphology; Figure 2 From the particle size distribution diagram, it can be seen that the volume fraction of the AlSi powder material prepared in this embodiment within the particle size range of ≤75μm is 98.04%, and the particle size content distribution of the AlSi powder material in D10, D50 and D90 is suitable, which is easier to adapt to the printing equipment. Figure 3 From the hollow ratio diagram, we can see that the hollow ratio of the prepared AlSi powder material is only 0.43%. This feature can make the printed device material more compact and further avoid the generation of pores during the printing process. Figure 4 In order to quantitatively characterize the sphericity of the obtained material, according to the obtained sphericity diagram, the sphericity of the AlSi powder material obtained by quantitative characterization is 85.8%. Good sphericity helps to improve the fluidity of the material during the printing process, ensure close bonding between layers, and make the material distribution more uniform.
[0054] (2) The AlSi powder material obtained above was used to print the product based on the laser selective melting additive manufacturing technology. The specific process parameters were: the oxygen content of the printing chamber was 0.08%, the pressure of the printing chamber was 25 mbar, the fan flow rate was 2.5 m / s, the substrate preheating temperature was 80°C, the thickness between the printing layers was 30 μm, the scanning spacing was 100 μm, the interlayer rotation angle was 67°, the scanning power was 260W, and the scanning speed was 1500 mm / s. The product was printed based on the above parameter control, and then the printed product was kept at 165°C for 6 hours to obtain an Al-Si alloy product.
[0055] Example 2
[0056] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-7Si-0.6Mg-0.4Sc-0.4Er-0.8Zr.
[0057] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-5Sc alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 850℃ for 20min, and then refined at 850℃ for 15min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 3.2 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, wait for the powder to cool down to room temperature 25°C, and then place the obtained powder on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm is ≥97.75%, and D10 is 21.7μm, D50 is 37.4μm, and D90 is 61.7μm, with a powder yield of 34%.
[0058] The AlSi powder material prepared in Example 2 was tested, and its SEM image is as follows: Figure 5 The particle size distribution diagram is shown in Figure 6 As shown, Figure 7 The hollow ratio diagram of AlSi powder material is shown. Figure 8 The sphericity diagram of AlSi powder material is shown. Figure 5 From the SEM image, it can be seen that the AlSi powder material prepared in this embodiment also has a good spherical morphology; Figure 6 From the particle size distribution diagram, it can be seen that the volume fraction of the AlSi powder material prepared in this embodiment within the particle size range of ≤75μm is 97.75%, and the particle size content distribution of the AlSi powder material in D10, D50 and D90 is suitable, and it is easy to adapt to the printing equipment. Figure 7 From the hollow ratio diagram, we can see that the hollow ratio of the prepared AlSi powder material is only 0.60%. This feature can make the printed device material more compact and further avoid the generation of pores during the printing process. Figure 8 In order to quantitatively characterize the sphericity of the obtained material, according to the obtained sphericity diagram, it can be seen that the sphericity of the AlSi powder material obtained by quantitative characterization is 82.7%. Good sphericity helps to improve the fluidity of the material during the printing process and make the material distribution more uniform.
[0059] (2) The AlSi powder material obtained above was used to print the product based on the laser selective melting additive manufacturing technology. The specific process parameters were: the oxygen content of the printing chamber was 0.08%, the pressure of the printing chamber was 25 mbar, the fan flow rate was 2.5 m / s, the substrate preheating temperature was 80°C, the thickness between the printing layers was 30 μm, the scanning spacing was 100 μm, the interlayer rotation angle was 67°, the scanning power was 280W, and the scanning speed was 1400 mm / s. The product was printed based on the above parameter control, and then the printed product was kept at 165°C for 6 hours to obtain an Al-Si alloy product.
[0060] Example 3
[0061] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-6.5Si-0.5Mg-0.1Sc-0.5Er-0.7Zr.
[0062] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh the corresponding amount of metal aluminum, metal magnesium, Al-20Si alloy, Al-5Sc alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 950℃ for 15min, and then refined at 950℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10Kg / min. After the atomization is completed, the powder is cooled to room temperature 25°C, and then the obtained powder is placed on an ultrasonic vibration screen for particle size screening to obtain AlSi powder material. The volume fraction of the AlSi powder material with a particle size range of ≤75μm is ≥97.46%, and D10 is 22.6μm, D50 is 38.4μm, and D90 is 61.9μm, and the powder yield is 26.7%.
[0063] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0064] Example 4
[0065] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-7.5Si-0.7Mg-0.5Sc-1.6Mn-0.1Er-1.1Zr.
[0066] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-5Sc alloy, Al-5Er alloy, Al-10Mn alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 850℃ for 30min, and then refined at 850℃ for 15min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥97.65%, and D10 was 22.5μm, D50 was 38.4μm, and D90 was 62.8μm, with a powder yield of 26.0%.
[0067] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0068] Example 5
[0069] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-7.5Si-0.7Mg-0.9Er-1.1Zr-1.6Mn.
[0070] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-10Mn alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is smelted at 900℃ for 30min, and then refined at 900℃ for 15min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥97.65%, and D10 was 23.1μm, D50 was 38.3μm, and D90 was 62.1μm, with a powder yield of 30.3%.
[0071] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0072] Example 6
[0073] (1) Prepare AlSi powder material, the composition and mass percentage of which are: Al-6.5Si-0.5Mg-1.4Er-0.7Zr.
[0074] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 950℃ for 15min, and then refined at 950℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥98.26%, and D10 was 25.4μm, D50 was 36.3μm, and D90 was 65.1μm, with a powder yield of 27.7%.
[0075] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0076] Example 7
[0077] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-6.5Si-0.7Mg-1.0Er-1.1Zr-1.2Mn.
[0078] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-10Mn alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 920℃ for 20min, and then refined at 920℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥97.84%, and D10 was 22.5μm, D50 was 37.0μm, and D90 was 63.2μm, with a powder yield of 29.3%.
[0079] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0080] Example 8
[0081] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-7.5Si-0.5Mg-1.4 Er-0.9Zr-1.6Mn.
[0082] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-10Mn alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 920℃ for 20min, and then refined at 920℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥98.20%, and D10 was 20.7μm, D50 was 37.5μm, and D90 was 61.9μm, with a powder yield of 33.3%.
[0083] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0084] Example 9
[0085] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-7.5Si-0.5Mg-0.95Er-0.85Zr-1.6Mn.
[0086] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-10Mn alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 920℃ for 20min, and then refined at 920℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥97.39%, and D10 was 22.7μm, D50 was 38.1μm, and D90 was 62.3μm, with a powder yield of 26%.
[0087] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0088] Example 10
[0089] (1) Prepare AlSi powder material, the composition and mass percentage of which are: Al-7.5Si-0.5Mg-1.25 Er-0.7Zr-1.6Mn.
[0090] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-10Mn alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 920℃ for 20min, and then refined at 920℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥98.12%, and D10 was 22.7μm, D50 was 39.1μm, and D90 was 62.1μm, with a powder yield of 28%.
[0091] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0092] Embodiment 11
[0093] (1) Prepare AlSi powder material, the composition and mass percentage of which are: Al-7.5Si-0.5Mg-1.0 Er-0.8Zr-1.6Mn.
[0094] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-10Mn alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 920℃ for 20min, and then refined at 920℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, wait for the powder to cool down to room temperature 25°C, and then place the obtained powder on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm is ≥97.54%, and D10 is 22.9μm, D50 is 37.0μm, and D90 is 62.3μm, and the powder yield is 25%.
[0095] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0096] Example 12
[0097] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-7.5Si-0.5Mg-1.2Er-0.8Zr-1.6Mn.
[0098] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-10Mn alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 920℃ for 20min, and then refined at 920℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥97.18%, and D10 was 22.6μm, D50 was 37.2μm, and D90 was 62.1μm, with a powder yield of 26%.
[0099] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0100] Embodiment 13
[0101] (1) Prepare AlSi powder material, whose components and mass percentages are: Al-6.5Si-0.5Mg-0.5Sc-0.5Er-0.7Zr.
[0102] First, wipe the inner wall, crucible and tundish of the gas atomization device with ethanol to remove impurities and moisture in the device. Weigh the corresponding amount of metal aluminum, metal magnesium, Al-20Si alloy, Al-5Sc alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 950℃ for 20min, and then refined at 950℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10Kg / min. After atomization, the powder was cooled to room temperature of 25°C, and then the obtained powder was placed on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm was ≥97.25%, and D10 was 22.3μm, D50 was 37.4μm, and D90 was 61.7μm, with a powder yield of 26.9%.
[0103] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0104] Embodiment 14
[0105] (1) Prepare AlSi powder material, the components and their mass percentages of which are: Al-6.5Si-0.5Mg-0.1Sc-0.4Er-0.7Zr.
[0106] First, wipe the inner wall, crucible and tundish of the gas atomization device with ethanol to remove impurities and moisture in the device. Weigh the corresponding amount of metal aluminum, metal magnesium, Al-20Si alloy, Al-5Sc alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 950℃ for 20min, and then refined at 950℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10Kg / min. After atomization, wait for the powder to cool down to room temperature 25°C, and then place the obtained powder on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm is ≥98.25%, and D10 is 23.3μm, D50 is 38.2μm, and D90 is 63.0μm, with a powder yield of 27.5%.
[0107] (2) The AlSi powder material obtained above is used to print a product according to the method described in Example 1 to obtain an Al-Si alloy product.
[0108] Embodiment 15
[0109] AlSi powder material was prepared by Example 1, and the parts were printed by laser selective melting additive manufacturing technology. The specific process parameters were as follows: the oxygen content of the printing chamber was 0.08%, the pressure of the printing chamber was 23 mbar, the fan flow rate was 2.3 m / s, the substrate preheating temperature was 80°C, the thickness between printing layers was 30 μm, the scanning spacing was 100 μm, the interlayer rotation angle was 67°, the scanning power was 260W, and the scanning speed was 1400 mm / s. The parts were printed based on the above parameter control, and then the printed parts were kept at 165°C for 8 hours to obtain Al-Si alloy parts.
[0110] Example 16
[0111] AlSi powder material was prepared by Example 1, and parts were printed by laser selective melting additive manufacturing technology. The specific process parameters were as follows: the oxygen content of the printing chamber was 0.1%, the pressure of the printing chamber was 27 mbar, the fan flow rate was 2.7 m / s, the substrate preheating temperature was 120°C, the thickness between printing layers was 50 μm, the scanning spacing was 120 μm, the interlayer rotation angle was 67°, the scanning power was 320W, and the scanning speed was 1800 mm / s. Parts were printed based on the above parameter control, and then the printed parts were kept at 200°C for 6 hours to obtain Al-Si alloy parts.
[0112] Comparative Example 1
[0113] (1) Prepare AlSi powder material, the composition and mass percentage of which are: Al-7Si-0.6Mg-0.8Er-0.8Zr.
[0114] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 920℃ for 20min, and then refined at 920℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, wait for the powder to cool down to room temperature 25°C, and then place the obtained powder on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm is ≥97.56%, and D10 is 23.7μm, D50 is 38.8μm, and D90 is 62.1μm, and the powder yield is 25%.
[0115] (2) The AlSi powder material obtained above was used to print the product based on the laser selective melting additive manufacturing technology. The specific process parameters were: the oxygen content of the printing chamber was 0.08%, the pressure of the printing chamber was 25 mbar, the fan flow rate was 2.5 m / s, the substrate preheating temperature was 80°C, the thickness between the printing layers was 30 μm, the scanning spacing was 100 μm, the interlayer rotation angle was 67°, the scanning power was 260W, and the scanning speed was 1500 mm / s. The product was printed based on the above parameter control, and then the printed product was kept at 165°C for 6 hours to obtain an Al-Si alloy product.
[0116] Comparative Example 2
[0117] (1) Prepare AlSi powder material, the composition and mass percentage of which are: Al-7Si-0.6Mg-1.2Er-0.8Zr.
[0118] First, wipe the inner wall of the gas atomization device, the crucible and the tundish with ethanol to remove impurities and moisture in the device. Weigh metal aluminum, metal magnesium, Al-20Si alloy, Al-5Er alloy and Al-10Zr alloy, and place them in the crucible according to the rule that the stacking density gradually decreases from bottom to top. Then the sealing of the device is tested. When the vacuum degree of the melting chamber and the atomization chamber is ≤50 Pa, the airtightness is considered to meet the standard. After the system is gas-replaced with argon gas with a purity greater than 99.99%, it is melted at 850℃ for 20min, and then refined at 850℃ for 10min. Then the refined aluminum alloy melt is poured into the tundish step by step for gas atomization powder making. The conditions for gas atomization powder making are argon as the atomizing gas, the atomization pressure is 2.5 MPa, the atomization temperature is 850℃, the atomization nozzle diameter is 5mm, and the atomization speed is 10 Kg / min. After atomization, wait for the powder to cool down to room temperature 25°C, and then place the obtained powder on an ultrasonic vibration sieve for particle size screening to obtain AlSi powder material. The volume fraction of AlSi powder material with a particle size range of ≤75μm is ≥97.23%, and D10 is 23.5μm, D50 is 37.1μm, and D90 is 63.4μm, with a powder yield of 25%.
[0119] (2) The AlSi powder material obtained above was used to print the product based on the laser selective melting additive manufacturing technology. The specific process parameters were: the oxygen content of the printing chamber was 0.08%, the pressure of the printing chamber was 25 mbar, the fan flow rate was 2.5 m / s, the substrate preheating temperature was 80°C, the thickness between the printing layers was 30 μm, the scanning spacing was 100 μm, the interlayer rotation angle was 67°, the scanning power was 260W, and the scanning speed was 1500 mm / s. The product was printed based on the above parameter control, and then the printed product was kept at 165°C for 6 hours to obtain an Al-Si alloy product.
[0120] Comparative Example 3
[0121] The AlSi powder material prepared in Example 1 was printed by laser selective melting additive manufacturing technology. The specific process parameters were as follows: the oxygen content of the printing chamber was 0.08%, the pressure of the printing chamber was 25 mbar, the fan flow rate was 2.5 m / s, the substrate preheating temperature was 80°C, the thickness between printing layers was 30 μm, the scanning spacing was 100 μm, the interlayer rotation angle was 67°, the scanning power was 340 W, and the scanning speed was 2000 mm / s. The printed parts were printed based on the above parameters, and then the printed parts were kept at 165°C for 6 hours to obtain Al-Si alloy parts. Obvious pores appeared in the obtained Al-Si alloy parts, and the maximum pore size reached 114 μm.
[0122] The components and contents of the AlSi powder materials prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were tested respectively, and the results are shown in Table 1. The above tests were mainly conducted using inductively coupled plasma mass spectrometry. It should be noted here that in the process of preparing the AlSi powder material, it is inevitable that there is an error between the component content of the AlSi powder material to be prepared and the component content of the AlSi powder material actually prepared. If the component content error is controlled within the range of ±0.1%, it can be considered that the error is within a reasonable range, and this error range is well known in the art.
[0123] Table 1
[0124]
[0125] The oxygen and nitrogen contents in the AlSi powder materials prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were tested respectively, and the sphericity and hollow powder rate of the prepared AlSi powder materials were tested. The results are shown in Table 2. Test methods for the above data:
[0126] Oxygen content and nitrogen content: The oxygen content and nitrogen content are characterized and measured using the ONH5500 oxygen, nitrogen and hydrogen analyzer; when the oxygen content in the material is controlled to be ≤400 ppm and the nitrogen content is ≤100 ppm, defects caused by oxidation in the subsequent printing process can be avoided.
[0127] Sphericity: The specific detection method refers to JY / T 0584-2020, and the characterization and determination are carried out using a scanning electron microscope. The sphericity is calculated specifically with reference to the standard operating procedure for particle characteristics of ASTM F1877-16.
[0128] Hollow powder rate: The specific inspection method refers to GB / T 13298-2015 Metal Microstructure Inspection Method, which includes randomly selecting 10 fields of view for photography and statistics under a 200× metallographic microscope after the sample is mounted, ground and polished.
[0129] Table 2
[0130]
[0131] The density, porosity, tensile strength, yield strength and elongation of the Al-Si alloy products prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were tested respectively, and the results are shown in Table 3. The test methods for the following data are as follows:
[0132] Density: After the sample was mounted, ground and polished, 15 fields of view were randomly selected under a 50× metallographic microscope for photography and statistical analysis using software.
[0133] Porosity: After the specimens were mounted, ground, and polished, 15 fields of view were randomly selected for photographing under a 50× metallographic microscope and statistically analyzed using software.
[0134] The test methods for tensile strength, yield strength and elongation are all based on GB / T 228.1-2010.
[0135] Table 3
[0136]
[0137] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0138] Table 1 shows the components of the AlSi powder materials to be prepared in Examples 1 to 16 and Comparative Examples 1 to 3 and the contents of the various components of the AlSi powder materials actually prepared. It can be seen from the data in the table that the content of the components of the AlSi powder materials prepared by the preparation method of the present invention is not much different from the content of the components of the materials to be prepared, and the content errors are all within the range of ±0.1%. However, in Comparative Example 2, since the smelting and refining temperatures in the preparation process are not within the preferred range of the present invention, the content of Zr in the AlSi powder materials actually prepared is significantly different from the designed components, and the content error even reaches 0.46%. Table 2 shows the oxygen content, nitrogen content, sphericity and hollow powder rate in the AlSi powder materials prepared in Examples 1 to 16 and Comparative Examples 1 to 3. It can be seen from the data in the table that in the AlSi powder materials prepared by the preparation method of the present invention, the oxygen content and nitrogen content can be controlled within a reasonable range; the sphericity and hollow powder rate in the AlSi powder materials are also at a good level.
[0139] Table 3 is the result of testing the performance of the Al-Si alloy parts obtained by printing the parts according to the corresponding method of the AlSi powder materials prepared in Examples 1 to 16 of the present invention and Comparative Examples 1 to 3. It can be seen from the data in the table that the density of the Al-Si alloy parts printed according to the part printing method of the present invention is ≥99.95%. In Comparative Example 3, during the part printing process, the printing parameters are not uniformly within the range of the present invention, so its density is worse, only 99.31%. The tensile strength, yield strength and elongation of the Al-Si alloy parts obtained in Examples 1 to 16 and Comparative Examples 1 to 3 are compared, and it is found that the above effects in Examples 1 to 16 are better, and they can have good tensile strength, yield strength, and good elongation. In particular, the tensile strength, yield strength and elongation of the Al-Si alloy parts prepared under the preferred conditions are better.
[0140] Comparative Example 1 is that the Er content in the AlSi powder material is not within the range described in the present invention, Comparative Example 2 is that the parameters in the preparation process of the AlSi powder material are uneven within the preferred range, and Comparative Example 3 is that the printing parameters in the part printing process are uneven within the range described in the present invention. The Al-Si alloy parts thus obtained cannot ensure that their tensile strength, yield strength and elongation are all within a good range, especially the elongation of the Al-Si alloy parts in the comparative example is much worse than that of the Al-Si alloy parts in the embodiments of the present invention.
[0141] In addition, in Examples 1, 5 to 12, metal Er is used to completely replace the metal Sc added in the AlSi powder material, and in Examples 2 to 4 and 13 and 14, metal Er is used to partially replace the Sc added in the AlSi powder material. The Al-Si alloy parts prepared from the AlSi powder material prepared in the above examples have good tensile strength, yield strength, and elongation, and good comprehensive performance. This shows that the preparation method of the present invention can indeed achieve the purpose of reducing its production cost while improving the performance of the AlSi powder material.
[0142] In summary, by simultaneously controlling the AlSi powder material composition, preparation method parameters and part printing parameters within the range described in the present invention, the prepared Al-Si alloy parts can have better tensile strength, yield strength and elongation. At the same time, the above-mentioned AlSi powder material also has the advantage of low preparation cost.
[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An AlSi powder material, characterized in that: In terms of weight percentage, the AlSi powder material includes the following components: Si: 6.5%~7.5%, Mg: 0.5%~0.7%, Zr: 0.7%~1.1%, Sc: 0.0%~0.5%, Mn: 0.0%~1.6%, Er and the balance Al; and when the Sc content is 0.0%, the Er content is 0.9%~1.4%, and the content ratio of Er to Zr is 1.1~1.8; when the Sc content is not 0.0%, the Er content is 0.0%~0.5%, and the sum of the Sc and Er contents is 0.8~1.0%.
2. The AlSi powder material according to claim 1, characterized in that: In terms of weight percentage, the AlSi powder material includes the following components: Si: 6.5%~7.5%, Mg: 0.5%~0.7%, Er: 1.0%~1.4%, Zr: 0.9%~1.1%, Mn: 1.2%~1.6%, and the balance is Al.
3. A method for preparing the AlSi powder material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Weigh the required alloy raw materials according to the content of the components to be prepared, place them in a smelting device, and make the vacuum degree of the smelting device ≤50Pa; After replacing the gas in the smelting device with an inert gas, the alloy raw material mixture is smelted and refined to obtain an aluminum alloy melt; The aluminum alloy melt is subjected to gas atomization powder making and particle size screening to obtain the AlSi powder material.
4. The method for preparing AlSi powder material according to claim 3, characterized in that: When the AlSi powder material contains metal Sc, the smelting temperature is 850-950°C, and the smelting time is 15-30 minutes; the refining temperature is 850-950°C, and the refining time is 10-15 minutes; When the AlSi powder material does not contain metal Sc, the smelting temperature is 900-950° C., and the smelting time is 15-30 min; the refining temperature is 900-950° C., and the refining time is 10-15 min; The raw materials in the smelting device are placed with a density gradually decreasing from bottom to top; The alloy raw materials include aluminum silicon alloy, aluminum erbium alloy, aluminum zirconium alloy, aluminum manganese alloy, metal aluminum, metal magnesium and optional aluminum scandium alloy; The inert gas is argon, and its purity is greater than or equal to 99.99%.
5. The method for preparing AlSi powder material according to claim 3 or 4, characterized in that: During the atomization powder making process, the atomization pressure is 2.5-3.2 MPa, the atomization temperature is 850-900° C., and the atomization gas is argon.
6. The method for preparing AlSi powder material according to claim 3 or 4, characterized in that: The volume fraction of the AlSi powder material having a particle size within the range of ≤75 μm is ≥97%.
7. An Al-Si alloy product, characterized in that: Prepared from the AlSi powder material according to claim 1 or 2.
8. A method for preparing an Al-Si alloy product according to claim 7, characterized in that: The Al-Si alloy part is obtained by using laser selective melting additive manufacturing technology to print the part and perform heat insulation treatment; The process parameters of the part printing are as follows: the oxygen content of the printing chamber is 0.08-0.1%, the pressure of the printing chamber is 23-27 mbar, the fan flow rate is 2.3 m / s-2.7 m / s, the substrate preheating temperature is 80-120°C, the thickness between printing layers is 30-50 μm, the scanning spacing is 100-120 μm, and the interlayer rotation angle is 67°; The temperature of the heat preservation treatment process is 165-200°C and the time is 6-8h; The scanning power during the printing process of the product is 260~320W; The scanning speed during the printing process of the product is 1400~1800 mm / s.
Citation Information
Patent Citations
AlSi7Mg powder material and preparation method and application thereof
CN107695338A
Al-Si-Mg-Sc-Zr aluminum alloy powder for laser additive manufacturing
CN112048647A
Rare earth erbium element reinforced AlSi7Mg aluminum alloy powder specially used for SLM, and application thereof
CN108486429A
Al-Si-Mg series aluminum alloy composition for selective laser melting technology and formed part preparation method
CN108486431A